Preparation method and application of copper-cobalt oxide Cu0. 92Co2. 08O4 with flower-shaped structure
By preparing the copper-cobalt oxide Cu0.92Co2.08O4 with a flower-like structure as a catalyst, the application problem of the lack of this catalyst in the prior art in catalyzing NaBH4 hydrolysis reaction is solved, and the effect of significantly improving the hydrogen generation rate in the NaBH4 hydrolysis reaction is achieved.
Patent Information
- Application Number
- CN202411662236.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
There is a lack of application reports on the use of copper-cobalt oxide Cu0.92Co2.08O4 as a catalyst in the hydrolysis of catalytic metal hydrides (such as NaBH4) in the prior art.
Using a preparation method of a flower-like copper-cobalt oxide Cu0.92Co2.08O4, a flower-like structured copper-cobalt oxide Cu0.92Co2.08O4 is used. By dissolving the cobalt source and the copper source in water, adding cationic surfactant, and performing a reduction reaction under an ice-water bath, the flower-like structured copper-cobalt oxide Cu0.92Co2.08O4 is then calcined.
The catalyst showed good catalytic performance in the NaBH4 hydrolysis reaction, which significantly improved the hydrogen production rate. Compared with the copper-cobalt oxide catalyst that has not been added or has not been added within a limited range, the hydrogen production rate has been significantly improved.
Smart Images

Figure CN119500137A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a copper-cobalt oxide Cu with a flower-like structure. 0.92 Co 2.08 O 4 Preparation method and application. Background Art
[0002] With the depletion of fossil energy and the increase of carbon dioxide emissions, the greenhouse effect problem is becoming more and more serious. In order to mitigate the impact on the global environment, hydrogen energy is regarded as an ideal choice for future energy due to its high combustion calorific value and zero carbon dioxide emissions. Therefore, it is particularly important to develop efficient and safe hydrogen storage materials.
[0003] Sodium borohydride (NaBH 4 ) has become the focus of research due to its high hydrogen storage capacity of 10.57wt%, stability in alkaline solution, and non-toxicity and recyclability of hydrolysis products. However, NaBH 4 The autohydrolysis reaction is very slow at room temperature. The use of catalysts can reduce the NaBH 4 The kinetic energy barrier of hydrolysis is reduced, thereby increasing the hydrogen production rate and reaction efficiency, making its application more controllable. At present, although precious metal catalysts (such as Pd and Ru) show good catalytic performance, their scarcity and high cost limit their industrial application. Therefore, finding low-cost and resource-rich non-precious metal catalysts has become an important direction to replace precious metal catalysts.
[0004] Among transition metal compounds, cobalt-based phosphides, borides and oxides have a strong affinity for NaBH 4 Hydrolysis shows good catalytic performance. In particular, the composite bimetallic catalyst, the bimetallic oxide catalyst prepared by in situ reduction and high-temperature calcination, shows a high hydrogen evolution rate due to its electron transfer and bimetallic synergistic effect. Therefore, in-depth research on non-precious metal bimetallic catalysts in NaBH 4 Its application in hydrogen production by hydrolysis will help promote the development of its industrial application.
[0005] Mingzhen Hu et al. provided a general template-free method to successfully synthesize Co 3 O 4 , CoO, Cu 0.92 Co 2.08 0 4 、MnCo 2 O 4.5 、ZnCo 2 O 4 and CuO, among which Cu 0.92 Co 2.08 04 、MnCo 2 O 4.5 and ZnCo 2 O 4 It presents a two-dimensional sheet structure and indicates that Co 3 O 4 etc. can catalyze the decomposition of hydrogen peroxide to produce oxygen (Hu et al., Template-free Synthesis of Mesoporous and Crystalline Transition Metal Oxide Nanoplates with Abundant Surface Defects, Matter 2, 1-16, May 6, 2020.). However, copper cobalt oxide Cu is not found in the prior art. 0.92 Co 2.08 O 4 As a catalyst in catalytic metal hydrides (such as NaBH 4 )Related reports on its application in hydrolysis to produce hydrogen. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a new flower-shaped copper-cobalt oxide Cu 0.92 Co 2.08 O 4 Preparation method and application of copper cobalt oxide Cu prepared by the method of the present invention 0.92 Co 2.08 O 4 As a catalyst for NaBH 4 The hydrolysis showed good catalytic performance.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A flower-like structure of copper-cobalt oxide Cu 0.92 Co 2.08 O 4 The preparation method specifically comprises: dissolving a cobalt source and a copper source in water, adding a cationic surfactant, stirring and dissolving to obtain a mixture; adding a reducing agent to the obtained mixture for reduction reaction, filtering after the reaction is completed, collecting the precipitate, washing with water until neutral, and obtaining a precursor; and calcining the obtained precursor to obtain the copper-cobalt oxide Cu with a flower-like structure. 0.92 Co 2.08 O 4 ;in,
[0009] The molar ratio of the cobalt source to the copper source is 3:1;
[0010] The cationic surfactant is one or a combination of two or more selected from CTAB (cetyltrimethylammonium bromide), DODMAC (dodecyldimethylammonium chloride), HTAC (cetyltrimethylammonium chloride), DDAB (dodecyldimethylbenzotriammonium chloride), benzalkonium chloride and stearalkonium chloride;
[0011] The amount of the cationic surfactant used is 0.59 to 0.75 times the molar amount of the cobalt source.
[0012] In the above technical solution, the cobalt source can be one or a combination of two or more selected from cobalt chloride, cobalt chloride hydrates (such as cobalt chloride hexahydrate, etc.), cobalt nitrate and cobalt nitrate hydrates (such as cobalt nitrate hexahydrate); preferably cobalt chloride or cobalt chloride hexahydrate.
[0013] In the above technical solution, the copper source can be one or a combination of two or more selected from cupric chloride, cupric chloride hydrates (such as cupric chloride monohydrate, cupric chloride dihydrate, cupric chloride trihydrate or cupric chloride tetrahydrate, etc.), cupric nitrate and cupric nitrate hydrates (such as cupric nitrate trihydrate, etc.); preferably cupric chloride.
[0014] In the above technical scheme, the selection and dosage of the reducing agent can be conventionally selected in the prior art. Specifically, the reducing agent can be one or a combination of two or more selected from sodium borohydride, lithium aluminum hydride and sodium bisulfite; the dosage of the reducing agent is usually in excess relative to the cobalt source. Preferably, the molar ratio of the cobalt source to the reducing agent is 1:1.5-3.
[0015] To avoid excessively violent reaction, the reduction reaction is preferably carried out in an ice-water bath; more preferably, the reducing agent is prepared into an aqueous solution and then added dropwise to the mixture for the reduction reaction.
[0016] In the above technical solution, calcination is preferably carried out at 300-500°C, and the calcination time is preferably 2-4 hours. Calcination is usually carried out in a muffle furnace.
[0017] The applicant found in the experiment that the amount of cationic surfactant used has an important influence on the catalytic activity of the obtained copper cobalt oxide. When the amount of cationic surfactant used is not within the above-defined range, the obtained copper cobalt oxide has a significant effect on the catalytic activity of NaBH 4 The rate of hydrogen production is significantly reduced during hydrolysis. Preferably, the amount of the cationic surfactant is 0.64 to 0.72 times the molar amount of the cobalt source. In a preferred embodiment, the amount of the cationic surfactant is 0.72 times the molar amount of the cobalt source.
[0018] Preferably, the cationic surfactant is CTAB.
[0019] In the present application, the water generally refers to deionized water. The amount of water used is preferably sufficient to dissolve all raw materials involved in the reaction. Preferably, based on 1 mmol of the cobalt source, the amount of water used for all raw materials is preferably controlled within 4 to 10 mL.
[0020] The present invention further includes the copper cobalt oxide Cu prepared by the above method 0.92 Co 2.08 O 4 Application in the preparation of hydrogen evolution catalysts, specifically in the preparation of metal hydride water decomposition hydrogen catalysts, more specifically in the preparation of NaBH 4 Application in water decomposition hydrogen catalyst.
[0021] Compared with the prior art, the present invention provides a method for preparing copper cobalt oxide Cu 0.92 Co 2.08 O 4 The new method, the electron microscope image shows that the copper cobalt oxide Cu prepared by this method 0.92 Co 2.08 O 4 The test results of the applicant show that the copper cobalt oxide Cu prepared by the method of the present invention 0.92 Co 2.08 O 4 As a catalyst for NaBH 4 The water decomposition hydrogen showed a good hydrogen evolution rate, which was higher than that of the copper cobalt oxide Cu without adding cationic surfactant or adding an amount not within the range specified in the present application. 0.92 Co 2.08 O 4 The hydrogen evolution rate is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The copper cobalt oxide Cu prepared in Example 1, Comparative Example 1-1, Comparative Example 1-2 and Comparative Example 1-6 of the present invention 0.92 Co 2.08 O 4 X-ray diffraction pattern of .
[0023] Figure 2 The copper cobalt oxide Cu prepared in Example 1 of the present invention 0.92 Co 2.08 O 4 Electron microscope image of .
[0024] Figure 3 For example 1 of the present invention, catalytic NaBH 4Schematic diagram of the water displacement test device used in the hydrolysis hydrogen production experiment; the numbers in the figure are: 1 round-bottom flask, 2 water bath, 3 gas washing bottle, 4 square sink, 5 electronic balance, 6 computer.
[0025] Figure 4 The copper cobalt oxide Cu prepared in Example 1 and Comparative Examples 1-1 to 1-6 of the present invention 0.92 Co 2.08 O 4 Catalytic NaBH 4 Volume-time relationship curve of hydrogen production during hydrolysis.
[0026] Figure 5 The copper cobalt oxide Cu prepared in Examples 2 to 6 of the present invention 0.92 Co 2.08 O 4 Catalytic NaBH 4 Volume-time relationship of hydrogen production during hydrolysis. DETAILED DESCRIPTION
[0027] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto.
[0028] Example 1
[0029] 528 mg (2.2 mmol) of cobalt dichloride hexahydrate and 100 mg (0.74 mmol) of anhydrous copper chloride were added to 10 ml of deionized water, stirred for 30 min, and then 582 mg (1.60 mmol) of CTAB (the molar ratio of the cobalt source to CTAB was 1:0.68) was added, and stirring was continued for 2 h. The resulting mixture was placed in an ice-water bath, and 6 mmol of sodium borohydride aqueous solution (concentration of 0.6 mol / L) was added dropwise. The mixture was stirred in an ice-water bath for 2 h, filtered, and the precipitate (black) was collected, washed with deionized water until neutral, and dried at 70°C to obtain a precursor; the precursor was placed in a muffle furnace, calcined at 400°C for 2 h, and cooled to obtain the copper cobalt oxide Cu 0.92 Co 2.08 O 4 .
[0030] The product obtained in this example has a black powder appearance. The product obtained in this example was subjected to X-ray diffraction and electron microscopy analysis. The XRD pattern and electron microscopy pattern are shown as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the product obtained in this example is determined to be Cu 0.92 Co 2.08 O 4 ,Depend on Figure 2 It can be seen that the product obtained in this example presents a regular hexagonal flower-like structure.
[0031] The catalytic NaBH 4 Hydrogen production process by hydrolysis, in which the schematic diagram of the drainage method test device is as follows Figure 3 The test method is as follows:
[0032] Prepare 50 mL of mixed solution (containing 0.6 wt% NaBH 4 +0.4wt%NaOH), immersed in a water bath at 30°C, then the powdered catalyst prepared in this example (10mg) was placed in the above mixed solution, stirred continuously, the catalytic reaction started, hydrogen was continuously generated, entered the washing bottle, and the discharged water was introduced into a square water tank placed on an electronic balance. The mass of the discharged water was recorded in real time by an online test system connected to a computer and converted into the drainage volume (i.e., the hydrogen production volume), and the hydrogen production rate was calculated using the following formula:
[0033] Hydrogen production rate = drainage volume (mL) / [catalyst mass (g) × catalytic time (t)]
[0034] The experimental results are as follows Figure 4 As shown. Figure 4 It can be seen that the catalytic NaBH 4 The hydrogen production rate is 3719.39 mL min -1 g -1 .
[0035] Comparative Example 1-1
[0036] 176 mg (0.74 mmol) of cobalt dichloride hexahydrate and 100 mg (0.74 mmol) of anhydrous copper chloride were added to 10 ml of deionized water and stirred for 30 min. Then, 182 mg (0.5 mmol) of CTAB (the molar ratio of the cobalt source to CTAB was 1:0.68) was added and stirred for 2 h. The resulting mixture was placed in an ice-water bath, and 6 mmol of sodium borohydride aqueous solution (concentration of 0.6 mol / L) was added dropwise. The mixture was stirred in an ice-water bath for 2 h, filtered, and the precipitate (black) was collected and washed with deionized water until neutral. The precursor was dried at 70 ° C to obtain the precursor. The precursor was placed in a muffle furnace, calcined at 300 ° C for 2 h, and cooled to obtain a copper cobalt oxide Cu with a black powder appearance. 0.92 Co 2.08 O 4 , its XRD pattern is as follows Figure 1 shown.
[0037] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH4 The hydrogen evolution rate of water decomposition is 1525.06 mL min -1 g -1 .
[0038] Comparative Example 1-2
[0039] 881 mg (3.70 mmol) of cobalt dichloride hexahydrate and 100 mg (0.74 mmol) of anhydrous copper chloride were added to 10 ml of deionized water and stirred for 30 min. Then, 364 mg (1.0 mmol) of CTAB (the molar ratio of the cobalt source to CTAB was 1:0.27) was added and stirred for 2 h. The resulting mixture was placed in an ice-water bath, and 6 mmol of sodium borohydride aqueous solution (concentration of 0.6 mol / L) was added dropwise. The mixture was stirred in an ice-water bath for 2 h, filtered, and the precipitate (black) was collected and washed with deionized water until neutral. The precipitate was dried at 70 ° C to obtain a precursor. The precursor was placed in a muffle furnace, calcined at 300 ° C for 2 h, and cooled to obtain a copper cobalt oxide Cu with a black powder appearance. 0.92 Co 2.08 O 4 , its XRD pattern is as follows Figure 1 shown.
[0040] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 2824.04 mL min -1 g -1 .
[0041] Comparative Examples 1-3
[0042] 881 mg (3.70 mmol) of cobalt dichloride hexahydrate and 100 mg (0.74 mmol) of anhydrous copper chloride were added to 10 ml of deionized water and stirred for 30 min. Then, 728 mg (2.0 mmol) of CTAB (the molar ratio of the cobalt source to CTAB was 1:0.54) was added and stirred for 2 h. The resulting mixture was placed in an ice-water bath, and 6 mmol of sodium borohydride aqueous solution (concentration of 0.6 mol / L) was added dropwise. The mixture was stirred in an ice-water bath for 2 h, filtered, and the precipitate (black) was collected and washed with deionized water until neutral. The precursor was dried at 70 ° C to obtain the precursor. The precursor was placed in a muffle furnace, calcined at 300 ° C for 2 h, and cooled to obtain a copper cobalt oxide Cu with a black powder appearance. 0.92 Co 2.08 O 4 .
[0043] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 1806.16mL·min -1 g -1 .
[0044] Comparative Examples 1-4
[0045] Example 1 was repeated, except that the amount of CTAB added was changed to 200 mg (1.2 mmol) (the molar ratio of the cobalt source to CTAB was 1:0.55).
[0046] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 .
[0047] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 2031.82 mL·min -1 g -1 .
[0048] Comparative Examples 1-5
[0049] Example 1 was repeated, except that the amount of CTAB added was changed to 620 mg (1.7 mmol) (the molar ratio of the cobalt source to CTAB was 1:0.55).
[0050] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 .
[0051] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 2554.08 mL min -1 g -1 .
[0052] Comparative Examples 1-6
[0053] Example 1 was repeated except that no CTAB was added.
[0054] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 , its XRD pattern is as follows Figure 1 shown.
[0055] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 1861.85 mL min -1 g -1 .
[0056] Example 2
[0057] Example 1 was repeated, except that the amount of CTAB added was changed to 474 mg (1.3 mmol) (the molar ratio of the cobalt source to CTAB was 1:0.59).
[0058] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 .
[0059] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 3305.58 mL·min -1 g -1 .
[0060] Example 3
[0061] Example 1 was repeated, except that the amount of CTAB added was changed to 510 mg (1.4 mmol) (the molar ratio of the cobalt source to CTAB was 1:0.64).
[0062] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 .
[0063] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 3558.0 mL min -1 g -1 .
[0064] Example 4
[0065] Example 1 was repeated, except that the amount of CTAB added was changed to 510 mg (1.6 mmol) (the molar ratio of the cobalt source to CTAB was 1:0.72).
[0066] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 .
[0067] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 5078.44 mL min -1 g -1 .
[0068] Example 5
[0069] Example 1 was repeated, except that the amount of CTAB added was changed to 601 mg (1.65 mmol) (the molar ratio of the cobalt source to CTAB was 1:0.75).
[0070] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 .
[0071] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 3857.55 mL min -1 g -1 .
[0072] Example 6
[0073] Example 1 was repeated except that cobalt nitrate was used instead of cobalt dichloride hexahydrate and copper nitrate trihydrate was used instead of anhydrous copper chloride.
[0074] Finally, the copper cobalt oxide Cu is obtained in the form of black powder. 0.92 Co 2.08 O 4 .
[0075] The copper cobalt oxide Cu obtained in this example was tested using the same testing device and method as in Example 1. 0.92 Co 2.08 O 4 Catalytic NaBH 4 The hydrogen evolution rate of water decomposition is 3506.81 mL·min -1 g -1 .
Claims
1. A flower-like structure of copper-cobalt oxide Cu 0.92 Co 2.08 The method for preparing O4 is characterized by: Dissolve a cobalt source and a copper source in water, add a cationic surfactant, stir and dissolve to obtain a mixture; add a reducing agent to the obtained mixture to carry out a reduction reaction, filter after the reaction is completed, collect the precipitate, wash with water until neutral, and obtain a precursor; calcine the obtained precursor to obtain the copper cobalt oxide Cu with a flower-like structure 0.92 Co 2.08 O4; among them, The molar ratio of the cobalt source to the copper source is 3:1; The cationic surfactant is one or a combination of two or more selected from CTAB, DODMAC, HTAC, DDAB, benzalkonium chloride and stearyl ammonium chloride; The amount of the cationic surfactant used is 0.59 to 0.75 times the molar amount of the cobalt source.
2. The preparation method according to claim 1, characterized in that: The cobalt source is one or a combination of two or more selected from cobalt chloride, cobalt chloride hydrate, cobalt nitrate and cobalt nitrate hydrate.
3. The preparation method according to claim 1, characterized in that: The copper source is one or a combination of two or more selected from copper chloride, copper chloride hydrate, copper nitrate and copper nitrate hydrate.
4. The preparation method according to claim 1, characterized in that: The reducing agent is one or a combination of two or more selected from the group consisting of sodium borohydride, lithium aluminum hydride and sodium bisulfite.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The reduction reaction was carried out in an ice-water bath.
6. The preparation method according to any one of claims 1 to 4, characterized in that: The calcination is carried out at 300-500°C.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The amount of the cationic surfactant used is 0.64 to 0.72 times the molar amount of the cobalt source.
8. The preparation method according to any one of claims 1 to 4, characterized in that: The cationic surfactant is CTAB.
9. The copper-cobalt oxide Cu prepared by the method according to any one of claims 1 to 8 0.92 Co 2.08 Application of O4 in the preparation of hydrogen evolution catalysts.
10. The use according to claim 9, characterized in that Application in the preparation of metal hydride water decomposition hydrogen catalyst.
Citation Information
Patent Citations
Preparation method of flaky cuprous oxide / cobaltous oxide nano composite material and application of flaky cuprous oxide / cobaltous oxide nano composite material in catalyzing hydrolysis of ammonia borane to produce hydrogen
CN111420664A
Preparation method and application of copper-copper oxide-copper cobaltate catalyst with adjustable oxygen vacancy content
CN112246244A
Preparation method of cobaltate nano composite material with bell structure, and application of cobaltate nano composite material in catalyzing hydrolysis of ammonia borane to produce hydrogen
CN112371127A